Підвищення ефективності очищення дифузійного соку з використанням гідроксиду алюмінію в нанорозмірному стані - Ткаченко, Сергій Володимирович (My University, 2014)
В дисертаційній роботі теоретично обґрунтована та експериментально підтверджена доцільність та ефективність використання гідроксиду алюмінію в нанорозмірному стані як додаткового реагенту для очищення дифузійного соку. Проведено детальне вивчення фізико-хімічних властивостей препарату гідроксиду алюмінію в нанорозмірному стані. In the thesis was theoretically proved and experimentally confirmed the expedience and efficiency of using aluminum hydroxide in the nanodimensional state as additional reagent for diffusion juice purification. A detailed study of the physicochemical characteristics of aluminum hydroxide preparation in the nanodimensional state was conducted, namely the reaction medium, the concentration of aluminum hydroxide in the preparation, the particle size of the solid phase, specific surface area of the solid phase, electrokinetic potential were defined and the chemical structure identification of the solid phase by nanosystems was conducted.
Keywords: коагуляція; дифузійний сік; очищення; нанореагент; нецукри; дисперсність; осадження; coagulation; purification; diffusion juice; nanoreagent; nonsugar; dispersion; precipitation